Simultaneous Estimation of Atorvastatin and Amlodipine by Reverse Phase High Performance Liquid Chromatography - Rajkondawar, V.V. (Asian Journal of Chemistry, 2010)
A simple, accurate, rapid, reproducible HPLC method has been developed for simultaneous estimation of atorvastatin and amlodipine using a mobile phase consisting 0.05 M potassium dihydrogen phosphate and acetonitrile in the ratio of 50 : 50 at a flow rate 1.0 mL/min. A Zorbax XDB 250 x 4.6 mm, C18 column was used as a stationary phase. Quantification was performed using UV detector at 235 nm. The method showed good resolution between two peaks. The result was validated by linearity and recovery studies.